2014
DOI: 10.1155/2014/752967
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Silicon Surface Passivation Achieved by Industrial Inductively Coupled Plasma Deposited Hydrogenated Intrinsic Amorphous Silicon Suboxide

Abstract: We present an alternative method of depositing a high-quality passivation film for heterojunction silicon wafer solar cells, in this paper. The deposition of hydrogenated intrinsic amorphous silicon suboxide is accomplished by decomposing hydrogen, silane, and carbon dioxide in an industrial remote inductively coupled plasma platform. Through the investigation on CO 2 partial pressure and process temperature, excellent surface passivation quality and optical properties are achieved. It is found that the hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…For the process, we employed TiCl 4 and H 2 O as the reactants and Ar (99.999%) as the purging gas. One cycle (one monolayer) of TiO 2 growth was 0.066 nm in thick and included eight steps, i.e., TiCl 4 reactant, pump-down, Ar purge, pump-down, H 2 O reactant, pump-down, Ar purge, and pump-down.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the process, we employed TiCl 4 and H 2 O as the reactants and Ar (99.999%) as the purging gas. One cycle (one monolayer) of TiO 2 growth was 0.066 nm in thick and included eight steps, i.e., TiCl 4 reactant, pump-down, Ar purge, pump-down, H 2 O reactant, pump-down, Ar purge, and pump-down.…”
Section: Methodsmentioning
confidence: 99%
“…One cycle (one monolayer) of TiO 2 growth was 0.066 nm in thick and included eight steps, i.e., TiCl 4 reactant, pump-down, Ar purge, pump-down, H 2 O reactant, pump-down, Ar purge, and pump-down. Due to the self-limiting growth of ALD, we grew four different thicknesses of TiO 2 thin films by controlling the cycle numbers (125, 250, 530, and 1000 cycles).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed description on the ICP platform is shown elsewhere [15]. Films of interest [a-Si:H(i) and a-SiO x :H(i)] were formed on both sides of (1 0 0) Czochralski Si wafers with a resistivity of 1-Ω · cm, while varying the process temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [15], and the contributions from Mueller et al [16]- [19], excellent surface passivation quality was shown by hydrogenated amorphous silicon suboxide [a-SiO x :H(i)] using different PECVD setups. It was demonstrated by Rattanapan et al [20] and others [21], [22] that a-SiO x :H(i) is able to suppress the epitaxial growth.…”
Section: Introductionmentioning
confidence: 99%